Eur/Usd exchange rate – can it be explained? - Fernandes, Cláudia Granjo (2018)
This paper estimates a present-value model suggested by Engel, Mark and West (2007) applied to the EUR/USD exchange rate for the period from 01/1999 to 12/2015. We present evidence that contrary to what expected, the variable output differential showed a negative impact on the EUR/USD exchange rate. Another interesting finding is the fact that when the sample is restricted to the period of European sovereign-debt crisis, explanatory variables have no longer statistical significance. In addition, in order to validate the performance of the model, we develop a VAR model to analyse the importance of the selected explanatory variables in the model to forecast EUR/USD exchange rate, as suggested by Meese and Rogoff (1982).